CONSEQUENCES OF EMOTIONAL NUTRITION AND TYPES OF EATING DISORDERS - Rositza Toncheva; Atanas Petkov; Yana Kashilska (Science & Research)

(untitled)
Over the past half century, people's eating habits have changed to such an extent that they have caused serious concern among doctors and nutritionists. They were joined by the concerns of psychologists, according to which the mental problems of modern man are largely due to unnatural diet and improper products. Numerous observations categorically prove that food is extremely important both for cognitive abilities (memory, perception, mental activity, imagination, etc.) and for the emotional and mental state of man. Interest in this area has grown tremendously in recent years as a result of the indisputable link between the eating habits of modern man and the many emotional and mental problems. The purpose of this article is to present systematic information on the problems of somatic and mental health arising from emotional nutrition. Methods - review of the scientific data, sociological methods. Overeating, hunger, excessive care for healthy eating are carriers of potential risk for the development of eating disorders - anorexia, bulimia, orthorexia, hyperphagia. Human behavior, including eating, exercise, and smoking, is often associated with a propensity for chronic psychological and psychosocial problems and also includes broader sociological and cultural discussions. People suffering from eating disorders must be consulted by a clinical psychologist, who will not only find the exact cause of this deviation, but also work in parallel with a nutritionist to successfully overcome it.